COVID-19 in the United States as affective frame - Protevi, John (Frontiers in Psychology, 2022)
In this paper I attempt to contribute to the developing field of “political philosophy of mind.” To render concrete the notion of “affective frame,” a social situation which pre-selects for salience and valence of environmental factors relative to a subject’s life, I conduct a case study of a deleterious socially instituted affective frame, which, during the early days of the Covid-19 pandemic in the United States, produced individuated circumstances that came crashing down on “essential workers” who were forced into a double bind. We saw here an untenable and ultimately fatal situation that forced a choice between, on the one hand, increasing the risk of their failing to provide financial support for their family if they quit their job or reduced their hours, and on the other, increasing their risk of contracting the virus by continuing to work. The case study will thus be itself an affective frame that will bring to the fore for its readers a nexus of harmful social practices of contemporary American society. Form is reinforced by content here, as this particular affective frame brings forth a further emphasis on affect when we focus on workers simultaneously socialized into roles as breadwinners and as members of the caring professions. For those people, quitting work becomes even more difficult as they come to affirm their self-identity of being providers of affective labor for those in their care at work and of being the affective anchor of family life at home, the one who financially helps keep a roof over the heads of their loved ones as well as being the emotional backbone of the family. Hence the affective frame of “essential workers in Covid times” renders salient and affirmatively valenced their affectively laden self-image as caring helpers of those in need, at home and at work.